Streetwalking LGBTQ Lives and protest in the Dominican Republic - Lara, Ana-Maurine (Critical Caribbean studies, 2021)
Streetwalking: LGBTQ Lives and Protest in the Dominican Republic is an exploration of the ways that lesbian, gay, bisexual, trans and queer persons exercise power in a Catholic Hispanic heteropatriarchal nation-state, namely the Dominican Republic. Lara presents the specific strategies employed by LGBTQ community leaders in the Dominican Republic in their struggle for subjectivity, recognition, and rights. Drawing on ethnographic encounters, film and video, and interviews, LGBTQ community leaders teach readers about streetwalking, confrontación, flipping the script, cuentos, and the use of strategic universalisms in the exercise of power and agency. Rooted in Maria Lugones's theorization of streetwalker strategies and Audre Lorde's theorization of silence and action, this text re-imagines the exercise and locus of power in examples provided by the living, thriving LGBTQ community of the Dominican Republic